Event shapes and azimuthal correlations in Z plus jets events in pp collisions at root s=7 TeV - Chatrchyan, S. (2013)
Measurements of event shapes and azimuthal correlations are presented for events where a Z boson is produced in association with jets in proton-proton collisions. The data collected with the CMS detector at the CERN LHC at root s = 7 TeV correspond to an integrated luminosity of 5.0 fb(-1). The analysis provides a test of predictions from perturbative QCD for a process that represents a substantial background to many physics channels. Results are presented as a function of jet multiplicity, for inclusive Z boson production and for Z bosons with transverse momenta greater than 150 GeV, and compared to predictions from Monte Carlo event generators that include leading-order multiparton matrix-element (with up to four hard partons in the final state) and next-to-leading-order simulations of Z + 1-jet events. The experimental results are corrected for detector effects, and can be compared directly with other QCD models. (c) 2013 CERN. Published by Elsevier B.V. All rights reserved.